PENERAPAN TEKNIK BUDIDAYA UNTUK MENURUNKAN KADAR NIKOTIN TEMBAKAU - Samsuri Tirtosastro; Pramono Sasongko (Universitas Tribhuwana Tunggadewi, 2016)
Tobacco still in mainstay of farmers, particularly in dry area, depleted of nutritions with irrigation rainfed. Nicotine levels can depressed through the implementation of cultivation techniques such as assembling new varieties of low-nicotine, choose a type of leaf tobacco and select the appropriate position on the stem, use limited of nitrogen fertilizers, decreased of plant populations, without trim and discard axillary buds and others. Currently, the design of cigarettes needs to be studied closely as the basis for a policies was still in order. Utilization of smoke filter, porous paper, and potential blooming tobacco need to be optimize to produce smoke-free nicotine without changing the quality. While this effort may cultivated, it may impact in loss productivity and sales value. Moreover, natural resources use have not equally optimal due to suppress the levels of nicotine tobacco